A mulher que comeu o mundo: Dramaturgia do ator e multiplicidade da cena - Icle, Gilberto (Latin American Theatre Review, 2007)
This article analyzes the process of creation of the play A mulher que comeu o mundo, from the Brazilian group Usina do Trabalho do Ator, in which the author of this paper is also the actor and director. There are many aspects to be considered in this text about the process of creation, such as the concept of actor as playwright or the dramaturgy of the performer and their effects on the scene. It also intends to discuss the differences and similarities between two versions of the same play (on stage and on street) and to analyze the function of the director as well as the ideas about the autonomy of art and of the actor. (GI, Article in Portuguese)